Psychometric properties of the Alcohol Use Disorders Identification Test (AUDIT) and prevalence of alcohol use among Iranian psychiatric outpatients - Simasadat Noorbakhsh; Jamal Shams; Mohamadmahdi Faghihimohamadi; Hanieh Zahiroddin; Mats Hallgren; Hakan Kallmen (BMC, 2018)
Abstract Background Iran is a developing and Islamic country where the consumption of alcoholic beverages is banned. However, psychiatric disorders and alcohol use disorders are often co-occurring. We used the Alcohol Use Disorders Identification Test (AUDIT) to estimate the prevalence of alcohol use and examined the psychometric properties of the test among psychiatric outpatients in Teheran, Iran. Methods AUDIT was completed by 846 consecutive (sequential) patients. Descriptive statistics, internal consistency (Cronbach alpha), confirmatory and exploratory factor analyses were used to analyze the prevalence of alcohol use, reliability and construct validity. Results 12% of men and 1% of women were hazardous alcohol consumers. Internal reliability of the Iranian version of AUDIT was excellent. Confirmatory factor analyses showed that the construct validity and the fit of previous factor structures (1, 2 and 3 factors) to data were not good and seemingly contradicted results from the explorative principal axis factoring, which showed that a 1-factor solution explained 77% of the co-variances. Conclusions We could not reproduce the suggested factor structure of AUDIT, probably due to the skewed distribution of alcohol consumption. Only 19% of men and 3% of women scored above 0 on AUDIT. This could be explained by the fact that alcohol is illegal in Iran. In conclusion the AUDIT exhibited good internal reliability when used as a single scale. The prevalence estimates according to AUDIT were somewhat higher among psychiatric patients compared to what was reported by WHO regarding the general population.